Comparison of Palliative Gastrectomy and Non-Gastrectomy in Advanced and Metastatic Gastric Cancer - Rakchob, Teerawut (The Thai Journal of Surgery, 2025)
Objective: A study was conducted to evaluate the efficacy of palliative gastrectomy (PG) compared to non-palliative gastrectomy (non-PG) in patients diagnosed with advanced or metastatic gastric adenocarcinoma, with an emphasis on survival outcomes and surgical complications. Materials and Methods: A retrospective cohort study was conducted involving patients diagnosed with advanced or metastatic gastric adenocarcinoma between January 2015 and August 2024 at Buri Ram Hospital, Buri Ram, Thailand. The patients were categorized into two groups: the PG group and the non-PG group (palliative surgical bypass or feeding enterostomy). Data analysis was performed, and a p-value of less than 0.05 was considered statistically significant. Results: A total of 136 patients were diagnosed with advanced or metastatic gastric cancer. The patients were divided into two groups: 61 patients in the PG group and 75 patients in the non-PG group. Chemotherapy was administered to 75 patients (55.2%). Among those who received chemotherapy, a higher proportion were from the PG group compared to the non-PG group, and this difference was statistically significant. (p < 0.001) Surgical complication was found in 24%. There was no significant difference in surgical complications between the two groups. (p = 0.757) The median survival time was 13 months for the PG group and 4 months for the non-PG group (HR: 0.28; 95% CI: 0.13-0.57; p = 0.001). Conclusion: Survival outcomes are markedly improved in patients who undergo PG without complications and receive subsequent chemotherapy.